Science Communication in Public Radio: The Case Study of MindTap - Greeves, Scott B.; Ledbetter, Rhesa N. (Frontiers in Communication, 2022)
Radio broadcasting is an integral medium for the public understanding of science. Yet, as a poorly recognized health disorder, mental health was not commonly discussed in U.S radio broadcasts until the early 1980s. Since then, mental health has increasingly been the subject of societal discourse and is now frequently the topic of focus for radio programming. Despite the increased attention on mental health, little academic inquiry has considered how science communicators may navigate locally complex and sensitive themes, such as those related to mental health. To address this gap, we discuss our experiences in producing a radio series on mental health called MindTap. Using the exemplar of MindTap, we explore models of science communication and their application within radio communication. Specifically, we suggest that topics, such as mental health, are best approached using the dialogue model of communication, which recognizes the value of integrating experiential and culturally situated knowledge with that of expert knowledge. We also illustrate how this form of communication supports narrative creation, and as such, identify practical insights for practitioners seeking to produce a mental health radio series.